Occupants' awareness of and satisfaction with green building technologies in a certified office building - Kim, Hye Gi; Kim, Sun Sook (Sustainability (Switzerland), 2020)
With growing awareness of the need to reduce greenhouse gas emissions, much effort has been made to achieve "sustainability" in the building sector. Across the globe, many architects and building owners are striving to realize mandatory or voluntary building certification, in order to affirm the environmental performance of their buildings. Various sustainable design strategies and green building technologies have been adopted to improve buildings' environmental performance as well as to achieve higher levels of certification. These technologies and strategies could affect building occupants' satisfaction as well as productivity. This paper presents the results of post occupancy evaluation (POE) surveys to investigate occupants' awareness of various green building technologies and their satisfaction levels and causes of dissatisfaction for selected technologies. A questionnaire survey was conducted for an office building in Korea that had received the highest grades in rating and certification systems. Some technologies showed higher levels of awareness and satisfaction, but there were also a few technologies with lower levels of satisfaction than we had expected. If these technologies are applied to buildings in the future, after improvisation or modification based on the POE results, it could serve as an effective strategy to increase people's satisfaction as well as improve environmental performance.
Keywords: Green building technologies; Occupant awareness; Occupant satisfaction; Post occupancy evaluation